2020
DOI: 10.1108/tr-03-2019-0085
|View full text |Cite
|
Sign up to set email alerts
|

Chinese cruise customers loyalty: the impact of customer participation and service personal values

Abstract: Purpose The purpose of this study is to further explore the effects of customer participation (CP) and service personal values (SPVs) on cruise customer satisfaction (CS) and customer loyalty (CL) by applying the empirical research approach. Design/methodology/approach A self-administered questionnaire was prepared and used to collect data. Exploratory factor analysis and structural equation modeling analysis was used to test the proposed model and hypotheses. Findings The empirical results indicate that C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 77 publications
(124 reference statements)
0
11
0
1
Order By: Relevance
“…Furthermore, this study revisits Umrah travelers' participation and Umrah travelers' loyalty because previous scholars' findings concerning the relationship between customer participation and customer loyalty have shown various results (Chan et al, 2010;Yim et al, 2012). Some scholars have reported that customer participation does affect customer loyalty (Wu et al, 2020), however, customer participation only impacts attitudinal loyalty, but not in the case of behavioral loyalty (Auh, et al, 2007;Cossío-Silva et al, 2016). Likewise, while customer participation includes member interaction and activity involvement, one study showed that member interaction does not significantly impact brand loyalty, while member interaction does (Hwang et al, 2018).…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Furthermore, this study revisits Umrah travelers' participation and Umrah travelers' loyalty because previous scholars' findings concerning the relationship between customer participation and customer loyalty have shown various results (Chan et al, 2010;Yim et al, 2012). Some scholars have reported that customer participation does affect customer loyalty (Wu et al, 2020), however, customer participation only impacts attitudinal loyalty, but not in the case of behavioral loyalty (Auh, et al, 2007;Cossío-Silva et al, 2016). Likewise, while customer participation includes member interaction and activity involvement, one study showed that member interaction does not significantly impact brand loyalty, while member interaction does (Hwang et al, 2018).…”
Section: Introductionmentioning
confidence: 91%
“…It also builds a better quality of relationship in service innovation (Sarmah and Rahman, 2018). Furthermore, customer participation positively influences the service personal value, satisfaction and loyalty of cruise customers (Wu et al, 2020). Although many scholars have explored the role of customer participation in creating customer loyalty, they have not investigated in the area of religious tourism.…”
Section: Introductionmentioning
confidence: 99%
“…The hotel industry under the change of institutional logic is also affected [7], directly affecting the quality of the tourism. There has been some research into tourists' emotional experiences, including how tourists may be attracted through appeal to emotions and the services provided at destinations [8][9][10][11], place attachment, and residents' attitudes and intentions toward tourism behavior [12]. How to effectively regulate holiday tourism to promote sustainable development and prevent significant negative impacts is a crucial issue that warrants the attention of national and local governments.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, tourism researchers have increasingly focused on Chinese customers, due to the vital role of the Chinese market and the rapid development of the cruise industry in China. The research topics investigated include customer motivations (Hsu and Li, 2017), servicescapes (Lyu et al , 2017), overall experience (Hung, 2018; Hung et al , 2020a), customer participation, personal values regarding service (Wu et al , 2019a) and onshore experience (Sun et al , 2019). Clearly, the cruise experience is an important topic that has gained increasing attention in recent years.…”
Section: Literature Reviewmentioning
confidence: 99%